2010
DOI: 10.4155/tde.10.47
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Nanoparticulate drug-delivery Systems for Treatment of Solid Tumors: a Review

Abstract: Technological advancements in the field of biomaterials, polymer chemistry and drug-delivery techniques have aided the development of a number of new drug-delivery systems for targeting to solid tumors. Numerous research groups have explored the possibility of utilizing tumor-specific drug-delivery systems using nanoparticles. In this review we have attempted to highlight the achievements of some research groups actively involved in nanoparticulate drug delivery systems. The manuscript presents an in-depth dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…2 Although a number of novel anticancer drugs have been developed, the use of existing drugs such as doxorubicin (Dox), paclitaxel and cisplatin are still predominant in the clinic. 3 More specifically, anthracycline drugs such as Dox are considered one of the most effective anticancer drugs ever developed. 4 It has been shown that Dox induces caspase-dependent apoptosis in cancer cells due to oxidative DNA damage in addition to topoisomerase II inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although a number of novel anticancer drugs have been developed, the use of existing drugs such as doxorubicin (Dox), paclitaxel and cisplatin are still predominant in the clinic. 3 More specifically, anthracycline drugs such as Dox are considered one of the most effective anticancer drugs ever developed. 4 It has been shown that Dox induces caspase-dependent apoptosis in cancer cells due to oxidative DNA damage in addition to topoisomerase II inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…The drug biodistribution can be suitably altered and side effects can be minimized by employing targeted delivery systems. A wide variety of drug carriers and passive and active targeting strategies have been reported in the literature 1 . However, upon reaching the intended site, the rate of drug release from the carriers is often very slow.…”
Section: Introductionmentioning
confidence: 99%
“…Nanodevices can be rationally designed to tailor functionality for a specific application. [15][16][17] Importantly, nanoparticles have been found to preferentially target phagocytic innate immune cells, 18,19 which makes them a compelling new generation of therapeutic agents to modulate inflammatory responses in specific tissues/organs. [11][12][13][14] Nanoparticles can also optimize therapeutic outcomes by improving in vivo biodistribution, achieving tissue/cell targeting, and sustaining the release of drugs.…”
mentioning
confidence: 99%